Ordovician chitinozoans and review on basin stratigraphy, biostratigraphy and paleobiogeography of northern Argentina along the Proto-Andean margin - de la Puente, Graciela Susana (2023)
Ordovician strata exposed across the Cordillera Oriental and the Sierras Subandinas in northwestern Argentina were part of a large retroarc foreland basin developed along the Proto-Andean margin within the Central Andes in South America. A revised chitinozoan biostratigraphy along and across-strike for the Tremadocian, Floian, Dapingian, Katian and Hirnantian stages, calibrated with other fossil groups in the basin, allow pinpointing the most characteristic events that affected the basin fill testing global versus local controls in accommodation, and suggesting comparisons with other peri-Gondwanan records. According to the chitinozoan data, the glacially-related Ordovician deposits in northwestern Argentina are restricted to the Hirnantian, and unconformably overlie late Katian deposits. In the Caspalá area (Cordillera Oriental), an interval with synsedimentary deformation and reworked chitinozoans correlate with glacially-related deposits in other sites of the eastern part of the basin (Río Capillas and Mecoyita areas). A glacial waning stage is determined by a thin interval of organic-rich black shales with sparse dropstones at the top of the Zapla Formation, containing Spinachitina oulebsiri associated with Desmochitina gr. minor, which together are typical latest Hirnantian components in other regions of Gondwana. Our study strengthens the foreland systems tract for the Ordovician Central Andean Basin with a volcanically fed interarc and foredeep depozone to the west (Puna region); a lower-accommodation forebulge depozone in the central area (mostly the Cordillera Oriental region); and a backbulge depozone (Sierras Subandinas and Sierras de Santa Bárbara) extending as far as the eastern Paraná Basin (reaching Paraguay and Brazil). Contemporaneous unconformities driven by global sea-level fluctuations were amplified or reduced due to deepening-narrowing or widening-shallowing, allowing contrasted accommodation, respectively associated to loading and relaxation. Ordovician chitinozoans from the Central Andean Basin indicate Northern, Western and peri-Gondwanan affinities, although locally some more cosmopolitan species described in Baltica, Avalonia and South China, are also recorded.